APPROXIMATION OF SOLUTIONS OF SPLIT INVERSE PROBLEM FOR MULTI-VALUED DEMI-CONTRACTIVE MAPPINGS IN HILBERT SPACES - Bello, A.U.; Chidume, C.E.; Isyaku, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2020)
Let H_{1} and H_{2} be real Hilbert spaces and A_{j} : H_{1} to H_{2}, (1 leq j leq r) be bounded linear linear operators, U_{i} : H_{1} to 2^{H_{1}}, (1 leq i leq n) and T_{j} : H_{2} to 2^{H_{2}}, (1 leq j leq r) be multi-valued demi-contractive operators. An iterative scheme is constructed and shown to converge weakly to a solution of generalized split common fixed points problem (GSCFPP). Under additional mild condition, the scheme is shown to converge strongly to a solution of GSCFPP. Moreover, our scheme is of special interest.